Assessment of Building Envelope Thermal Performance Using Overall Thermal Transfer Value (OTTV) at Labuang Baji Hospital, Makassar - Syamsuddin Mustafa; Syamfitriani Asnur; Andi Besse Opu (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Hospitals are public service buildings with high energy consumption because they operate continuously and require stable thermal comfort. One aspect that affects building energy efficiency is the performance of the building envelope in resisting heat transfer from the outdoor environment. This study examines the Overall Thermal Transfer Value (OTTV) as an indicator of energy efficiency in Building B of Labuang Baji Hospital, Makassar. The assessment was conducted through field observation and measurement of building-envelope parameters, including façade orientation, wall area, glazing area, material type, thermal transmittance, shading conditions, and solar radiation entering the indoor spaces. OTTV analysis was carried out on the fourth, fifth, and sixth floors with reference to SNI 6389:2020, which specifies a maximum OTTV limit of 35 W/m². The results indicate that the average OTTV values ranged from 81.04 W/m² on the fourth floor to 85.93 W/m² on the fifth floor, all of which substantially exceeded the national standard. The northwest façade consistently recorded the highest average OTTV values (92.80–94.03 W/m²), whereas the south façade exhibited the lowest values (69.00–74.38 W/m²), although these also remained well above the allowable limit. These findings demonstrate that the existing building envelope has not yet achieved the required level of thermal efficiency and contributes to increased cooling loads. The results also identify the northwest façade and upper floors as priority targets for energy retrofit interventions. Recommended improvement measures include the use of high-performance glazing, the installation of external shading devices, optimization of the window-to-wall ratio, and improved wall insulation to reduce heat gain and enhance overall building energy efficiency.